2017
DOI: 10.1038/bjc.2017.171
|View full text |Cite
|
Sign up to set email alerts
|

Tumour heterogeneity poses a significant challenge to cancer biomarker research

Abstract: Background:The high degree of genomic diversity in cancer represents a challenge for identifying objective prognostic markers. We aimed to examine the extent of tumour heterogeneity and its effect on the evaluation of a selected prognostic marker using prostate cancer as a model.Methods:We assessed Gleason Score (GS), DNA ploidy status and phosphatase and tensin homologue (PTEN) expression in radical prostatectomy specimens (RP) from 304 patients followed for a median of 10 years (interquartile range 6–12). GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 37 publications
4
104
0
Order By: Relevance
“…suggested that the intratissue variability is a likely reason for this disappointing discrepancy . The tissue heterogeneity is indeed one of the most recognized challenges for accurate diagnostication and prognostication in PCa …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that the intratissue variability is a likely reason for this disappointing discrepancy . The tissue heterogeneity is indeed one of the most recognized challenges for accurate diagnostication and prognostication in PCa …”
Section: Discussionmentioning
confidence: 99%
“…Although grades 2 and 3 have equivalent Gleason sums equal 7, the latter has significantly worse prognosis based on a higher amount of pattern 4 . Although the ISUP grade system has led to more accurate prognostication, the tumor heterogeneity and subjective variations in biopsy sampling and interpretation of the GS still impact the patient outcome and treatment decisions . One of the main goals in PCa research is to discover new molecules to accurately stratify PCa patients with indolent from aggressive tumors.…”
Section: Introductionmentioning
confidence: 99%
“…A further goal for future work is to explore (and exploit) the heterogeneity of tumor evolution in greater depth: this heterogeneity aids the evasion of the tumor from immune effects. Studying the consequences of decanalization [48] during cancer progression is too-often sidelined, despite evidence supporting its prominence [4951]. Yet despite these challenges, for which the complexity of the disease may be often in part responsible, great progress has been and continues to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic and transcriptomic analyses have provided insight into the complexity of prostate tumors and the existence of molecular subtypes. However, the clinical applicability of these classifications has been thwarted, due in part to the highly heterogeneous nature of PCa and the difficulty of identifying additional relevant alterations that occur at low frequencies (11)(12)(13)(14)(15)(16)(17)(18) (60). We hypothesized that heterogeneously expressed genes can expose unidentified molecular subclasses of PCa and/or identify translationally relevant gene sets.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical heterogeneity of PCa reflects, in part, a remarkable genomic heterogeneity (11)(12)(13)(14)(15)(16)(17)(18). This suggests that disease stratification based on molecular features may be of prognostic value beyond standard clinicopathological variables, and aid in the clinical management of the disease, as is the case for other cancers, i.e.…”
Section: Introductionmentioning
confidence: 99%